A novel storage and tunable light source generated by a soliton pulse in a micro ring resonator system for super dense wavelength division multiplexing use - Khunthong Sarapat; Jalil Ali; P. P. Yupapin (My University, 2009)
Abstract We propose a novel system of a dense wavelength division operation using the nonlinear microring resonators system that can be used to generate the broad output light spectra, whereas the significant increase in channel capacity is obtained. A system consists of two micro and a nanoring resonators incorporating an add/drop filter that can be integrated into a single system. The large bandwidth signal is generated by using a soliton pulse propagating within a Kerr type nonlinear medium. The obtained results have shown the potential of using such system for broad band light source generation, amplification, storage, and regeneration, whereas the amplified signals can be stored within a nanowaveguide, which is allowed to form the regeneration of the broad light spectra after amplification. The advantage is that the specific wavelength of the broadband source, for instance, 1.50 μm can provide the super dense wavelength division multiplexing channels, whereas the increase in channel capacity of 1000 times is achieved. © 2009 Wiley Periodicals, Inc. Microwave Opt Technol Lett 51: 2948–2952, 2009; Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/mop.24807
Keywords: Nanoring; Photonic and Optical Devices